Application of hybrid real-time power system simulator for setting up and close loop testing of protection and control equipment; IFOST 2012; Vol. 2 - Prokhorov A. V. Anton Viktorovich (2012, 2012)
This paper presents new tool for setting up and comprehensive close loop testing of protection, automation and control equipment (PACE). The role of this tool for Smart Grid (SG) design process is also described. Comprehensive close loop tests of PACE in power system (PS) various regimes with consideration of possible interactions between tested equipment and other automation are possible only with the use of real-time software and hardware simulators. But digital simulators are based on numerical methods of integration and therefore impose constraints on differential order and stiffness of a mathematical model of PS. Besides, each step of differential equation integration causes the error which is accumulated and cannot be eliminated. Because of this a simulation time is very restricted and simulation itself can never be continuous. New capabilities are provided with the use of a hybrid simulation concept which has no mentioned limitations. The concept of hybrid simulation was created at Tomsk Polytechnic University and became a base for construction of Hybrid Real-Time Power System Simulator (HRTSim). HRTSim is a multipurpose tool suitable for various power engineering tasks, among which are PACE setting up and testing. Practical results of HRTSim application in the Tyumen PS are presented in this paper. HRTSim was used there for testing and setting up of momentary and sustained fast turbine valving control (FTVC) systems of the generating unit of the Surgut co-generation power plant.